Mucoadhesive In Situ Gelling Liquid Crystalline Precursor System to Improve the Vaginal Administration of Drugs - de Araújo, Patricia Rocha [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; da Silva, Isabel Cristiane [UNESP]; de Paula Zago, Lucas Henrique [UNESP]; Oshiro Junior, João Augusto; Pavan, Fernando Rogério [UNESP]; Ribeiro, Anderson Orzari; Fontana, Carla Raquel [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2019)
The vaginal mucosa is a very promising route for drug administration due to its high permeability and the possibility to bypass first pass metabolism; however, current vaginal dosage forms present low retention times due to their dilution in vaginal fluids, which hampers the efficacy of many pharmacological treatments. In order to overcome these problems, this study proposes to develop a mucoadhesive in situ gelling liquid crystalline precursor system composed of 30% of oleic acid and cholesterol (7:1), 40% of ethoxylated and propoxylated cetyl alcohol, and 30% of a dispersion of 16% Poloxamer 407. The effect of the dilution with simulated vaginal fluid (SVF) on this system was evaluated by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), rheological studies, texture profile analysis (TPA), mucoadhesion study, in vitro drug release test using hypericin (HYP) as drug model, and cytotoxicity assay. PLM and SAXS confirmed the formation of an isotropic system. After the addition of three different concentrations of SVF (30, 50, and 100%), the resultant formulations presented anisotropy and characteristics of viscous lamellar phases. Rheology shows that formulations with SVF behaved as a non-Newtonian fluid with suitable shear thinning for vaginal application. TPA and mucoadhesion assays indicated the formation of long-range ordered systems as the amount of SVF increases which may assist in the fixation of the formulation on the vaginal mucosa. The formulations were able to control about 75% of the released HYP demonstrating a sustained release profile. Finally, all formulations acted as safe vaginal drug delivery systems.
Keywords: drug delivery system; liquid crystalline system; mucoadhesion; nanotechnology; vaginal administration